Policies and measures to mitigate the potential environmental impacts of cross-border infrastructure projects in Asia - ZhongXiang Zhang (Asian Development Bank Institute (ADBI), 2011)
While bringing positive impacts and benefits, cross-border infrastructure projects face additional challenges relative to national projects. Moreover, such projects involve a variety of technical, regulatory, institutional, and legal factors, and their obstacles constrain the development of cross-border infrastructure projects. This paper argues that proper technical specifications and well-functioning regulatory, institutional and legislative/legal frameworks with clearer lines of oversight are crucial to getting such projects off the ground in the first place and to ensure that they operate properly and reliably while minimizing their environmental impacts. It is pointed out that many issues in theses areas need to be addressed at the national level. The paper concludes that such domestic efforts, coupled with regional frameworks and arrangements wherever necessary, will promote the further development of cross-border infrastructure projects.
Keywords: O13; Q01; Q43; Q48; Q53; Q54; Q56; Q58; R48; 330; Infrastrukturinvestition; Internationale Zusammenarbeit; Institutionelle Infrastruktur; Welt